The effect of three verbal stimuli on fluency in stutterers - Vijayalakshmi AR (Journal of All India Institute of Speech and Hearing, 1970)
The present study has attempted to answer the question 'What effect do the three Verbal stimuli "Good" "No" and "Zehu" have on the fluency aspect of stutterer's verbal behaviour?'